2020
DOI: 10.1017/s0007114520003669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary choline on liver lipid composition, liver histology and plasma biochemistry of juvenile yellowtail kingfish (Seriola lalandi)

Abstract: Choline plays a crucial role in lipid metabolism for fish, and its deficiency in aquafeed has been linked to compromised health and growth performance. A 56-d experiment was conducted to examine the effects of dietary choline on lipid composition, histology, and plasma biochemistry of yellowtail kingfish (Seriola lalandi; YTK; 156 g initial body weight). The dietary choline content ranged from 0.59 to 6.22 g/kg diet. Three grams of 2-amino-2-methyl-1-propanol (AMP)/kg was added to diets, except for a control d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 98 publications
3
8
0
Order By: Relevance
“…However, in the absence of reference ranges or indication of pathology, elevated levels of these enzymes may indicate their activity level in the plasma rather than liberation from cell lysis. This is consistent with Liu et al (50) , who found elevated LD for the fastest growing yellowtail kingfish in their study, consistent with its role in energetics. Likewise, the elevated AST levels for fish fed higher levels of Met found in our study are likely due to altered amino acid metabolism rather than pathology.…”
Section: Plasma Biochemistrysupporting
confidence: 93%
See 1 more Smart Citation
“…However, in the absence of reference ranges or indication of pathology, elevated levels of these enzymes may indicate their activity level in the plasma rather than liberation from cell lysis. This is consistent with Liu et al (50) , who found elevated LD for the fastest growing yellowtail kingfish in their study, consistent with its role in energetics. Likewise, the elevated AST levels for fish fed higher levels of Met found in our study are likely due to altered amino acid metabolism rather than pathology.…”
Section: Plasma Biochemistrysupporting
confidence: 93%
“…However, in the absence of reference ranges or indication of pathology, elevated levels of these enzymes may indicate their activity level in the plasma rather than liberation from cell lysis. This is consistent with Liu et al (50) , who found elevated LD for the fastest growing YTK in their study, consistent with its role in energetics.…”
Section: Plasma Biochemistrysupporting
confidence: 93%
“…It should be pointed out that the liver is an indicative organ to evaluate the nutritional and physiological status of fish, and imbalanced nutrition intake can cause disorders of liver function and clinical changes in histological status (Peng et al, 2022). In the present study, both AST and ALT activities in serum were relatively stable with the enhancement of dietary lipid, denoting that if not beneficial, this amount of lipid in this present study is probably not detrimental to juvenile Yangtze sturgeon (Liu et al, 2021). Despite that fish did not exhibit signs of “fatty liver”‐related syndrome (e.g.…”
Section: Discussionsupporting
confidence: 50%
“…Since the 1990s, extensive research in Japan has focused on artificial breeding and breeding technology for S. lalandi ( Sano, 1998 ). In China, aquaculture of S. lalandi began in 2001 ( Jiang et al, 2001 ), along with biological research, including studies of embryogenesis, seedling cultivation, and effects of salinity stress on growth ( Shi et al, 2019 ; Xu et al, 2019 ; Liu A et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%